An Analysis on English Textbook Entitled Bahasa Inggris Based on Tomlinson's Theory - Fakhomah, Desy Nur, Drs. Djoko Srijono, M.Hum (2017)
This research paper is aimed to investigate the compatibility of materials in the textbook Bahasa Inggris based on Tomlinson's theory. It also investigates whether the materials in the textbook support students' language skill or not in English teaching learning process. The writer uses descriptive research as the type of the study. The data of the study are the content of English textbook entitled Bahasa Inggris. The analysis is done by using Three Level of Analysis by Littlejohn (2011). They are: 1) Level 1 Analysis: 'What is There' (Objective Description), 2) Level 2 Analysis: 'What is Required of Users' (Subjective Analysis), and 3) Level 3 Analysis: 'What is Implied' (Subjective Inference). The result of this study shows that the English textbook Bahasa Inggris fulfills 15 criteria or 93,75% of Tomlinson's theory and caters 3 language skills (speaking, reading and writing). It means that the textbook is suitable to be used by the students.